Toward an International Curricula Network for exchanges and LifeLong Learning - Thiriet, J. M.; Meriaudeau, F.; Burguillo, J. C.; Fremont, H.; Yahoui, H.; de Fooz, P. (Elektronika ir Elektrotechnika, 2010)
The ELLEIEC ERASMUS thematic network runs from October 2008 to September 2011. This project deals with several aspects linked to LifeLong Learning in Electrical and Information Engineering in Europe. One of the actions of the project is to set some ICN (International Curricula Networks) in some disciplines (specialities in EIE) and levels (Bachelor or Master) aiming at defining the necessary learning outcomes for some curricula. It is defined and agreed at the European level by the ICNs and can be used for AEL (Accreditation of Experience Learning) for European workers who want to validate some diploma, corresponding to their actual knowledge and skills. AEL could be partial, so it is crucial to have the possibility, for workers who need it, to validate some modules; these modules can be prepared either in a classical class or remotely. The modules (or pieces of modules) which are available remotely to students, and agreed by the partners of the ICN, are called IM (International Modules).